Thyrotoxicosis in Erbil Governorate - Abdula, Taher; Jokel, Azad (Sulaimani Journal for Pure and Applied Sciences, 2001)
A prospective study of 120 cases with goitre seen in surgical department in Rizgery Teaching Hospital in Erbil form the first Nov. 1997 to demonstrate the incidence oftlryrotoxicosis among goitrous patients. We also tried to show inciden of thyrotoxicosis in relation to Age, Sex, Residency, frequency of symptoms and signs(we had concentrated on the following symptoms: Neck swelling, Excessive sweating, Nervousness, Palpitation, Hot intolerance Weight lose; and the following signs: Moist hands, Tachycardia, Fine finger tremor, & Eye signs). Twenty Patients(16.6%) with goitres proved to be thyrotoxic, 10 patients of the thyrotoxies (50%) were in the third decade of life. Female to male ratio was(4:1). All of them had neck swelling, while excessiv sweating, nervousness and hot intolerance present in 90% of patients. Palpitation and weight loss were present in 83.3%.
Keywords: Iodine deficiency; goitre; Lipiodolloione supplementation,toxic goitre